2006
DOI: 10.1177/0583102406065898
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Vibration-based Structural Health Monitoring with Special Emphasis on Composite Materials

Abstract: Structural health monitoring and damage detection techniques are tools of great importance namely in the offshore, civil, mechanical and aeronautical engineering communities, either due to safety reasons or to the economical benefits it may bring. The need for detecting damage in complex structures has led to the development of a vast amount of techniques, in particular those based upon structural vibration analysis. In the present article, some of the latest advances in Structural Health Monitoring and Damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
257
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(260 citation statements)
references
References 61 publications
2
257
0
1
Order By: Relevance
“…The detailed analysis of the most of them can be found in the excellent review articles [4][5][6][7] …”
Section: Modal Based Methodsmentioning
confidence: 99%
“…The detailed analysis of the most of them can be found in the excellent review articles [4][5][6][7] …”
Section: Modal Based Methodsmentioning
confidence: 99%
“…SHM technology is applied increasingly for research and industrial purposes as a potential tool for quality assurance [18,19]. However, many of the developed and available NDE technologies are complex, expensive and require significant calibration with the passage of time.…”
Section: Structural Health Monitoring (Shm) Is a Type Of A Non-destrumentioning
confidence: 99%
“…The former includes methods based on acoustic emission [3,4], operational load monitoring [1,5] and impact detection techniques [1,[6][7][8][9][10]. The latter covers various methods based on vibration analysis [11][12][13][14] and non-destructive techniques, such X-ray [15,16], shearography [1,17], vibro-thermography [18,19], ultrasonic and acousto-ultrasonic testing [20,21], and guided ultrasonic waves [22][23][24][25][26]. Recent years have brought research interest in various damage-related nonlinear phenomena that can be observed in ultrasonic responses and vibration characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…frequency response function, transfer function) can be used to detect structural damage, as reviewed in [11][12][13][14]. An excellent overview of vibration-based methods-that also cover nonlinear approaches-can be found in [41][42][43].…”
Section: Introductionmentioning
confidence: 99%